2019
DOI: 10.1101/gr.248435.119
|View full text |Cite
|
Sign up to set email alerts
|

Deep profiling and custom databases improve detection of proteoforms generated by alternative splicing

Abstract: Alternative pre-mRNA splicing has long been proposed to contribute greatly to proteome complexity. However, the extent to which mature mRNA isoforms are successfully translated into protein remains controversial. Here, we used highthroughput RNA sequencing and mass spectrometry (MS)-based proteomics to better evaluate the translation of alternatively spliced mRNAs. To increase proteome coverage and improve protein quantitation, we optimized cell fractionation and sample processing steps at both the protein and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…A substantial contribution of alternative splicing to gene expression changes induced by T cell activation was initially recognized in 2007 13,15 . More recently, it has been shown that a number of AS changes in activated T cells translate to differential protein isoform expression and changes in T cell function 16,33,34 . T cell activation-dependent AS changes impact genes that modulate a range of T cell processes, from signaling, migration or fate decisions, to proliferation 15,19,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial contribution of alternative splicing to gene expression changes induced by T cell activation was initially recognized in 2007 13,15 . More recently, it has been shown that a number of AS changes in activated T cells translate to differential protein isoform expression and changes in T cell function 16,33,34 . T cell activation-dependent AS changes impact genes that modulate a range of T cell processes, from signaling, migration or fate decisions, to proliferation 15,19,35 .…”
Section: Discussionmentioning
confidence: 99%
“…AS therefore provides an important layer of gene expression programming control, by diversifying the proteins that are actually encoded within genes. Previous work from the Lynch lab has established that antigenic/TcR stimulation modulates the AS gene expression pattern of T cells 13,15,16 as revealed by RNA-Seq, quantitative microarray, bioinformatics and RT-PCR analyses. The resulting protein isoforms have been linked to functional outcomes such as TcR α chain transcription 17 , TcR signal transduction 18 and JNK-CELF2 dependent splicing control 19 , indicating AS plays crucial functional roles in activated T cell biology.…”
Section: Introductionmentioning
confidence: 99%
“…However, evaluating how many of the detected transcripts are translated and functional in the cell remains challenging (Wang et al, 2018;Kim et al, 2014). This difficulty has stimulated the development of integrative approaches combining gene annotations, RNA-seq data and also data generated by other high-throughput techniques (Marti-Solano et al, 2020;de la Fuente et al, 2020;Louadi et al, 2020;Ait-hamlat et al, 2020;Agosto et al, 2019;Sterne-Weiler et al, 2018;Denti et al, 2018;Tapial et al, 2017;Tranchevent et al, 2017;Weatheritt et al, 2016;Ezkurdia et al, 2015;Rodriguez et al, 2013;Gonzàlez-Porta et al, 2013;De La Grange et al, 2010) toward a better characterisation of the AS landscape. Recent studies underscore AS functional impact and contribution to protein diversity (Marti-Solano et al, 2020;Agosto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, identifying variant peptides was performed by parsing variant calls into peptides (e.g., tryptic peptides) and then appending those peptides to the database [11][12][13][14][15] . This approach precludes the identification of full length proteoforms, and so in this work, we apply variations to the entire protein sequence.…”
Section: Introductionmentioning
confidence: 99%